Apoptotic Effects of a Thioether Analog of Vitamin K3 in a Human Leukemia Cell Line. (December 2021) - Asami, Satoru; Suzuki, Mikana; Nakayama, Toshimitsu; Shimoda, Yasuyo; Miura, Motofumi; Kato, Koichi; Tokuda, Eiichi; Ono, Shinichi; Kawakubo, Takashi; Nishizawa, Kenji; Yamanaka, Kenzo; Suzuki, Takashi
Research suggests that thioether analogs of vitamin K3 (VK3 ) can act to preserve the phosphorylation of epidermal growth factor receptors by blocking enzymes (phosphatases) responsible for their dephosphorylation. Additionally, these derivatives can induce apoptosis via mitogen-activated protein kinase and caspase-3 activation, inducing reactive oxygen species (ROS) production, and apoptosis. However, vitamin K1 exhibits only weak inhibition of phosphatase activity, while the ability of VK3 to cause oxidative DNA damage has raised concerns about carcinogenicity. Hence, in the current study, we designed, synthesized, and screened a number of VK3 analogs for their ability to enhance phosphorylation activity, without inducing off-target effects, such as DNA damage. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-Diphenyltetrazolium Bromide (MTT) assay revealed that each analog produced a different level of cytotoxicity in the Jurkat human leukemia cell line; however, none elicited a cytotoxic effect that differed significantly from that of the control. Of the VK3 analogs, CPD5 exhibited the lowest EC50, and flow cytometry results showed that apoptosis was induced at final concentrations of ≥10 μM; hence, only 0.1, 1, and 10 μM were evaluated in subsequent assays. Furthermore, CPD5 did not cause vitamin K-attributed ROS generation and was found to be associated with a significant increase in caspase 3 expression, indicating that, of the synthesized thioether VK3 analogs, CPD5 was a more potent inducer of apoptosis than VK3 . Hence, further elucidation of the apoptosis-inducing effect of CPD5 may reveal its efficacy in other neoplastic cells and its potential as a medication.